2020
DOI: 10.4314/sajas.v50i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Carcass, physicochemical and sensory characteristics of meat from genetic reserve ducks after two reproductive seasons

Abstract: The aim of the study was to compare carcass composition and meat quality of i) Pekin ducks of French origin (P9), ii) crosses of wild mallard and Pekin duck (K2), and iii) crosses of Khaki Campbell drakes and Orpington Fauve ducks (KhO1). Twenty carcasses from 110-week-old ducks of each genetic group were used. Carcass weight of P9 was significantly higher than that of K2 and KhO1. Carcasses of K2 ducks had a significantly lower percentage of neck and leg muscles and giblet weight compared with P9 and KhO1 duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…Considering the scientific literature, Kokoszy ński et al [9] demonstrate significant differences in the percentage of pectoral muscles and fat in carcasses of 8-week-old Pekin ducks from genetic resources of (conservative herds) P33 (Polish Pekin), P8 (Danish Pekin) and P9 (French Pekin). Pekin ducks from P33 (Polish Pekin), P8 (Danish Pekin) and LsA (English Pekin) herds at 110 weeks of age did not differ in the percentage of carcass components [23], which may indicate the disappearance of diversification among the studied duck flocks, and is consistent with the results of our research. In turn, Kokoszy ński et al [23] observed a higher proportion of breast muscle and leg muscle, and a lower proportion of abdominal fat in the carcasses of 110-week-old P9 ducks compared to 113-week-old P9 ducks.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Considering the scientific literature, Kokoszy ński et al [9] demonstrate significant differences in the percentage of pectoral muscles and fat in carcasses of 8-week-old Pekin ducks from genetic resources of (conservative herds) P33 (Polish Pekin), P8 (Danish Pekin) and P9 (French Pekin). Pekin ducks from P33 (Polish Pekin), P8 (Danish Pekin) and LsA (English Pekin) herds at 110 weeks of age did not differ in the percentage of carcass components [23], which may indicate the disappearance of diversification among the studied duck flocks, and is consistent with the results of our research. In turn, Kokoszy ński et al [23] observed a higher proportion of breast muscle and leg muscle, and a lower proportion of abdominal fat in the carcasses of 110-week-old P9 ducks compared to 113-week-old P9 ducks.…”
Section: Discussionsupporting
confidence: 91%
“…Pekin ducks from P33 (Polish Pekin), P8 (Danish Pekin) and LsA (English Pekin) herds at 110 weeks of age did not differ in the percentage of carcass components [23], which may indicate the disappearance of diversification among the studied duck flocks, and is consistent with the results of our research. In turn, Kokoszy ński et al [23] observed a higher proportion of breast muscle and leg muscle, and a lower proportion of abdominal fat in the carcasses of 110-week-old P9 ducks compared to 113-week-old P9 ducks. In turn, Lewczuk and Gornowicz [31] reported a higher percentage of pectoral muscles and leg muscles in the carcass of 10week-old P9 ducks (in total, 30.44% males, 29.26% females) compared to the results of these studies (27.8% in P9 males, and 26.9% in females in relation to the weight of the gutted carcass with the neck).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations